2021
DOI: 10.1021/acs.nanolett.1c03142
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tunable Enhancement and Switching of Nonlinear Emission from All-Inorganic Lead Halide Perovskites via Electric Field

Abstract: Herein, we demonstrate a highly tunable enhancement and switching of nonlinear emission from all-inorganic metal halide perovskites based on an asymmetrically biased metal− insulator−semiconductor (MIS) structure. We achieve 2 orders of magnitude enhancement of the two-photon-pumped photoluminescence (TPL) from CsPbBr 3 microplates with the MIS structure, due to comprehensive effects including localized field effect, trapfilling effect, and collection enhancement. In particular, taking advantage of electric-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It is worth noting that the reported NLO molecular switches mainly refer to the single response switches based on the conversion between bistable states, 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] that is, single-pole single-throw (SPST) switches. There is little for multi-response ones, i.e., single-pole double (multi)-throw or double (multi)pole single (double, multi)-throw switches.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the reported NLO molecular switches mainly refer to the single response switches based on the conversion between bistable states, 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] that is, single-pole single-throw (SPST) switches. There is little for multi-response ones, i.e., single-pole double (multi)-throw or double (multi)pole single (double, multi)-throw switches.…”
Section: Introductionmentioning
confidence: 99%
“…, 7,8 great efforts have been devoted to discovering and characterizing different NLO molecular switching materials. 7,9–30 Recently, based on the characteristics of alkalides and electrides, we have also achieved a series of NLO molecular switches. 23–27 The famous alkalide 31,32 and electride 33 are excess electron compounds, in which alkali metal(s) and localized electron(s), respectively, act as anions for the former and the latter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the 'soft' ionic nature of perovskites and their strong susceptibility to their environment, [122][123][124][125][126][127][128][129][130] the fabrication conditions 89,[131][132][133] and post-fabrication treatments [134][135][136][137][138][139][140] can be utilized to influence the device performance. To date, most perovskite-sensitized bilayer devices have been fabricated by two-step solution-based methods, where RubDBP is deposited onto the underlying perovskite film from either toluene (TOL) or chlorobenzene (CB), known antisolvents for perovskite syn-thesis to avoid dissolution of the underlying perovskite thin film.…”
Section: Fabrication Methods and Surface Treatmentsmentioning
confidence: 99%
“…Several studies have been performed on dual optical-electrical excitation, and devices with different structures have been explored, i.e., vertical LED structures with , and without current injection, a horizontal transistor structure, and a metal–insulator–semiconductor structure . These previous results found that electrical stimulation either did not effect or had an adverse effect on amplified spontaneous emission (ASE) and lasing thresholds, even though photoluminescence (PL) enhancement , upon electrical excitation has been observed (this was attributed to trap filling). In contrast to the above work, we find a reduction (by a factor of 3) in the ASE threshold when a positive voltage over 4 V is applied to CsPbBr 3 perovskite LEDs.…”
mentioning
confidence: 99%